2020
DOI: 10.1093/ofid/ofaa153
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Level May Predict the Risk of COVID-19 Aggravation

Abstract: Background. Clinical findings indicated that a fraction of coronavirus disease 2019 patients diagnosed as mild early may progress to severe cases. However, it is difficult to distinguish these patients in the early stage. The present study aimed to describe the clinical characteristics of these patients, analyze related factors, and explore predictive markers of the disease aggravation.Methods. Clinical and laboratory data of nonsevere adult COVID-19 patients in Changsha, China, were collected and analyzed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
210
4
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(267 citation statements)
references
References 14 publications
27
210
4
26
Order By: Relevance
“…High CRP values have now become synonymous with severe COVID-19 infection among adults as seen in majority of the studies. 28,29,30 Mean CRP in our study was found to be 10.98mg/dl. CRP as high as 153.77mg/dl were seen in asymptomatic children while CRP as low as 4.59mg/dl was seen in the severe case suggesting a milder immune response.…”
Section: Discussionsupporting
confidence: 41%
“…High CRP values have now become synonymous with severe COVID-19 infection among adults as seen in majority of the studies. 28,29,30 Mean CRP in our study was found to be 10.98mg/dl. CRP as high as 153.77mg/dl were seen in asymptomatic children while CRP as low as 4.59mg/dl was seen in the severe case suggesting a milder immune response.…”
Section: Discussionsupporting
confidence: 41%
“…Inflammatory markers, which have been widely used in diagnosing infections and predict disease progression [ 26 ], were investigated in several reports since the beginning of the COVID-19 pandemic. CRP, which is a protein produced by the liver, was found to be a relatively good predictor for the development of pneumonia in MERS-CoV infections [ 27 ] and has recently been found to be a valuable marker to anticipate the possibility of aggravation of non-severe adult COVID-19 patients, with an optimal threshold value of 26.9 mg/L [ 28 ]. This association is also replicated in our cohort, in which we found an above-normal CRP is associated with severe disease requiring ICU admission (OR = 21.1, 95% CI: 1.19–374) but was not associated with mortality ( p -value = 0.143).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of reports from China have also detailed C-reactive along with D-dimers, coagulation times, and lactate dehydrogenase; with lower platelet and lymphocyte counts a common nding in " Cytokine Storm Syndrome " in hospitalized patients with COVID-19 [13]. Others have also analysed CRP to look for association with the disease aggravation showed that CRP was signi cantly associated with aggravation of nonsevere COVID-19 patients [14]. Elevated levels of these in ammatory markers found in the our study group concur to these hypothesis.…”
Section: Discussionmentioning
confidence: 99%